2014
DOI: 10.1097/shk.0000000000000100
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal Hypertension in Medical Critically Ill Patients

Abstract: Intra-abdominal hypertension/abdominal compartment syndrome (IAH/ACS) is a well-recognized entity among surgical subspecialties. Nevertheless, it has been proven to be present in the medical critically ill population. Prospective and retrospective observational studies have found medical patients with IAH/ACS to be associated with death in the intensive care unit and other poor outcomes. Frequently, it is underdiagnosed and undertreated in this patient group. Limitations encountered in these observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Although the adverse effects of IAH have received much attention, the effects of slightly elevated IAPs remain unclear. Despite critically ill patients, the intraperitoneal pressures in adults are rarely more than 5–7 mmHg [13] – [16] , which is within the acceptable normal range for such patients [1] , [17] . In fact, based on the IAH diagnostic standards (12 mmHg for adults and 10 mmHg for children), 60% of adults in the intensive care unit have slightly elevated IAPs of 5–12 mmHg; the corresponding range for children is approximately 4–10 mmHg [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the adverse effects of IAH have received much attention, the effects of slightly elevated IAPs remain unclear. Despite critically ill patients, the intraperitoneal pressures in adults are rarely more than 5–7 mmHg [13] – [16] , which is within the acceptable normal range for such patients [1] , [17] . In fact, based on the IAH diagnostic standards (12 mmHg for adults and 10 mmHg for children), 60% of adults in the intensive care unit have slightly elevated IAPs of 5–12 mmHg; the corresponding range for children is approximately 4–10 mmHg [1] .…”
Section: Introductionmentioning
confidence: 99%
“…A great number of pathophysiological changes occur due to IAH, including an increase in thoracic pressure and CVP, a decrease in the returned blood volume and a compensatory increase in the HR, and finally respiratory failure, which calls for ventilatory support (22)(23)(24). The present study demonstrated that compared with those obtained by PCV, the PIP, P mean and Cst were significant improved, all which is beneficial to the respiratory system of patients, with PRVCV.…”
Section: Discussionmentioning
confidence: 99%
“…28 Elevated IAP compresses the IVC and results in smaller and unreliable IVC parameters. For example, a patient with fluid overload may develop IAH or ACS due to ascites or bowel edema and present with reduced renal output or hypotension.…”
Section: Intra-abdominal Pressurementioning
confidence: 98%